Is There Possibility Of Withdrawal Seizure In Opioid Dependence Syndrome? A Case Report (Journal of Psychiatrists' Association of Nepal, 2020)
Opioids are commonly used and abused substance worldwide. Opioid withdrawal may manifest as severe muscle cramps, diarrhea, rhinorrhea, lacrimation, piloerection, yawning, and fever. Here, we report a 32 year old man with heroin dependence, presented with new onset generalized tonic-clonic seizure following heroin withdrawal. Seizure is a life-threating condition and rare phenomenon in opioid withdrawal therefore, reporting of this case is important. It may help clinician to be aware and consider seizure as a part of opioid withdrawal.